Identifying and Prioritizing Factors Affecting Financing Performance of The Supply Chain in Food Industry SMEs - Mahdi Imani Bashokoh; Esmaeil Malek Akhlagh; Mohammad Hasan Gholizadeh; Amirreza Soori; Amin Ghasemi Sahebi; Samira Gholami (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
Chain financing is one of the essential pillars of the supply chain, which plays a critical role in facilitating and accelerating the financing of the working capital of the production company. This research aims to identify and prioritize the factors affecting the financing performance of the supply chain in food industry SMEs of Guilan province in Iran. At first, indicators were selected by browsing the library and academic sources, then releasing Likert Scale questionnaires between experts to find effective scales. Using the Analytic Hierarchy Process (AHP), the importance of 7 categories, such as the cultural index of human resources, infrastructure technical, macro policy, financial, legal, logistics, financial, and information technology, respectively, and a total of 38 sub-factors are prioritized. The results show that the development of accreditation and rating institutions in the discussion of chain financing; Development of chain financing tools and infrastructures in operationalizing it in the country's banking network; Creating electronic invoice infrastructure and store terminals; Emphasizing the regulatory role of the Central Bank and the development of supply chain management companies under the supervision of the industry are the most critical factors. Based on the identified factors, a hierarchical model of chain financing in SME food industries is proposed, with which businesses can formulate action plans for financing problems along their supply chain.